Does Sex Discordance on Antenatal Ultrasound Always Predict Dichorionicity? - Kai Chen; David C Merrill; Guo-Yang Luo; Dan-Dan Shi (Wolters Kluwer Health, 2020)
Abstract. Monochorionic dizygotic twin gestation is clinically very uncommon but poses significant antenatal and postnatal complications. Here we review the diagnosis, mechanism, perinatal management, and pregnant outcomes of monochroic dizygotic twin gestation.